Nyari Haleuangna Manjing Dongkarina: Dongkari and the Vocal–Instrumental Aesthetic System of Tembang Sunda Cianjuran - Mohamad Yusuf Wiradiredja; Arif Budiman (Institut Seni Indonesia Denpasar, 2026)
This study examines the aesthetics of Tembang Sunda Cianjuran as a relational vocal–instrumental performance system shaped through reciprocal interaction between panembang (vocalists) and pamirig (instrumental accompanists) within the principal Cianjur–Bandung lineage. Previous scholarship has largely emphasized vocal technique and performer excellence, while the broader relational, instrumental, and integrative dimensions of Cianjuran aesthetics have remained insufficiently theorized. This research aims to formulate an integrative aesthetic framework grounded in the concept of dongkari as Cianjuran’s foundational normative principle, encompassing dongkari haleuang (vocal formation), dongkari lagu (melodic structure and ornamentation), and dongkari pirigan (instrumental relationality). Employing an interpretative qualitative design with an emic, practice-based methodology, the study draws upon more than five decades of embodied practitioner experience, intergenerational in-depth interviews with leading vocal and instrumental tradition bearers, and critical literature analysis. Data were interpreted through an adaptive operationalization of A.A.M. Djelantik’s aesthetic theory of form, content, and presentation, recontextualized according to the indigenous performance logic of Cianjuran. The findings reveal that Tembang Sunda Cianjuran aesthetics are fundamentally relational, proportional, and affectively regulated rather than virtuosity-centered, synthesized through kesepakatan perasaan (shared affective agreement) as the central aesthetic mechanism governing real-time musical coherence. The study contributes methodologically by demonstrating the value of integrating embodied emic inquiry into musicological analysis, and theoretically by positioning kesepakatan perasaan as an indigenous framework that enriches broader debates on relational aesthetics, intersubjective musical attunement, and cross-cultural performance studies.